Revelasi Allah pada Sulang Silima Pakpak dalam Hidup Menggereja Umat - Paulinus Tibo; Ronika Tindaon (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2022)
Humans in life are parts of their culture. In their culture humans grow and develop and find meaning of their lives in society. This concept is inseparable from the kinship system in Sulang Silima Pakpak which maintains culture as local wisdom. This study aims to find the revelation of God in Sulang Silima Pakpak and its contribution to Church’s life. The research approach is qualitative which consists of observation, interview and documentation. The research target is the West Pakpak tribal community. The research findings show that the kinship system in Sulang Silima has values in accordance with moral values in the teachings of the Catholic Church and therefore, is relevant to the life and development of the faith of the people.